Brief report: can COVID-19 infection trigger rheumatoid arthritis-associated autoimmunity in individuals at risk for the disease? A nested cohort study - Lamacchia, Celine; Gilbert, Benoit; Studer, Olivia; Lauper, Kim; Finckh, Axel (Frontiers in Medicine, 2023)
Objectives: To investigate the association between severe acute respiratory syndrome-associated coronavirus-2 (SARS-CoV-2) infection and subsequent development of autoimmunity or pre-clinical manifestations associated with rheumatoid arthritis (RA) in at risk population. Methods: This is a nested study within a prospective cohort of first-degree relatives of RA patients (RA-FDR). Participants are tested for RA-associated autoantibodies (anti-citrullinated peptide antibodies (ACPA) / rheumatoid factor (RF)) and clinical signs and symptoms suggestive of early disease. SARS-CoV-2 infections were self-reported between March 2020 and January 2023. All individuals with a pre-pandemic (sample 1) and a post-pandemic sample (sample 2) were included in the analysis. The exposure of interest was self-reported SARS-CoV-2 infection. The primary outcome was a clinically significant change in RA-associated autoantibody serum titers. Secondary outcomes included: becoming seropositive, becoming symptomatic, developing classifiable RA. Results: Among 168 RA-FDRs, 109 reported a SARS-CoV-2 infection between sample 1 and sample 2. During this period, 2 RA-FDRs (1.2%) became anti-CCP2 seropositive, none became anti-CCP3 IgG positive, 6 (3.6%) became RF IgM seropositive, 1 became (0.6%) RF IgA seropositive, 19 (11.3%) became symptomatic and none developed classifiable RA. SARS-CoV-2 infection was not significantly associated with increases in RA autoantibody titers or with secondary outcomes. Conclusions: We could not detect an association between SARS-CoV-2 infection and subsequent development of RA-associated autoimmunity, nor signs or symptoms of RA in an at risk population. These findings do not support the hypothesis that SARS-CoV-2 infections triggers the immune onset of RA.